Barriers to Report Patient Safety Incidents in Hospital: Scoping Review - Rosiana Kusuma; Chriswardani Suryawati; Daru Lestantiyo (GLOBAL HEALTH SCIENCE GROUP, 2024)
Patient safety incident reporting is part of the patient safety programme. At the hospital level, this reporting is to find out the causes of patient safety incidents and find the root causes to anticipate that the incident will not happen again. According to the National Reporting and Learning System (NRLS) report, from August 2021 to July 2022, there were 2,410,311 reports of patient safety incidents in the UK. According to Malaysian Ministry of Health (MoH) data, there were 151,225 reports of patient safety incidents in 2021. The purpose of this scoping review is to evaluate the current literature on barriers to reporting patient safety incidents and summarise evidence relating to differences in barriers to reporting patient safety incidents in Indonesian and overseas hospitals. This research uses the scoping review method. Scoping review is a method used to identify literature comprehensively through various sources with various research methods and related to the research topic. The results showed that the barriers in reporting patient safety incidents are Management Support, Lack of Education and Training, Patient Safety Knowledge, Safety Motivation, Workload, Coworker Support. Barriers to reporting patient safety incidents, both in hospitals in Indonesia and abroad, have similar problems.